The Culture of Transactional Politics in Indonesia’s Gubernatorial Elections Since Reformation - Amin, Muryanto (International Journal of Criminology and Sociology, 2021)
Since initiating political reform in 1998, Indonesia has sought to restructure its political institutions and processes as a means of reinforcing public autonomy. This article explores the three direct gubernatorial elections that have occurred in North Sumatra since the process was first implemented, namely in 2008, 2013, and 2018. We interviewed key actors, including gubernatorial candidates, political party leaders, and electoral agents, and analyzed the cultural practices of corruption and bribery. The first three local elections’ examinations of North Sumatra reveal that transactional politics occurred through the practice of corruption and exchange of public offices, thereby having a deleterious effect on public services of the North Sumatra Provincial Government. Moreover, local culture tends to accept to provision and receipt of bribes and gratuities during local elections. This study contributes to the discourse on the beliefs and practices that go against the values of democracy and threaten established political systems.